The Influence Of Personal Capability, Technological Sophistication And Utilization Of Technology On Accountant Performance With The Effectiveness Of Accounting Information Systems As An Intervening Variable In Riau Islands Shipping Companies - Eko Prihananto; Bambang Satriawan; Robin Robin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the direct and indirect effect of personal capability, sophistication and utilization of technology on accountant performance with the effectiveness of accounting information systems as an intervening variable in riau islands shipping COMPANIES. The population in this study were all accountants owned by shipping companies under the auspices of the Indonesian National Shipowners' Association Riau Islands, namely 31 companies and each company had at least 2 finance department people. So that the population in this study were 103 respondents. To get a sample that describes the population, this research uses a saturated sample method, where the entire population is sampled, namely 103 accountants. The results of this study personal capability has a positive and significant effect on the accounting information system. Technological sophistication has a positive and significant effect on the accounting information system. Utilization of technology has a positive and significant effect on the accounting information system. Personal capability has a positive and significant effect on accountant performance. Technological sophistication has a positive and significant effect on accountant performance. Utilization of technology has a positive and significant effect on accountant performance. Accounting information system has a positive and significant effect on accountant performance. Personal capability indirectly has a significant effect on accountant performance through the accounting information system. In other words, personal capability significantly mediates the relationship between personal capability and accountant performance. Personal capability indirectly has a significant effect on accountant performance through accounting information system. In other words, technological sophistication significantly mediates the relationship between technological sophistication and accountant performance. Indirect utilization of technology has a significant effect on accountant performance through accounting information system. In other words, technology utilization significantly mediates the relationship between technology utilization and accountant performance.